PERMIAN STRATIGRAPHY AND FUSULINIDS FROM ROSH GOL (CHITRAL, E HINDU KUSH) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1993)
Chitral (Pakistan), geologically, includes the eastern termination of the Hindu Kush and its transition to the Karakorum. The position of the boundary is not precisely defined, and may be located provisionally at the Chitral Fault, or at the Tirich Mir Fault. Four main tectonostratigraphic units are identified. From SE to NW they are:1) Lun Shales (shales and slates with Devonian calcareous intercalations) and Devonian to Permian carbonates. 2) Metabasites, consisting of amphibolites and green tuffs, locally associated with carbonates. 3) Atark Group, mostly metacarbonates in which Permian, Triassic and Cretaceous intervals have been detected. 4) Wakhan Slates, a very thick terrigenous succession of dark colour, partly of Paleozoic age. Huge granitoid bodies have been intruded into this unit. This 4-fold subdivision is here proposed for the first time. A terrigenous-calcareous succession of Permian age has been measured and sampled in the Atark Group at Rosh Gol. Seven lithostratigraphic units have been identified. Six of them contain fossils, mostly fusulinids, allowing identification of Yahtashian, Bolorian, Kubergandian and Late Murgabian or Midian. The most significant species of fusulinids are illustrated; these have close affinities to the Central Pamir.
Keywords: Permian; Fusulinida; Stratigraphy; Hindu Kush; Pakistan.